Slip-driven MHD nanofluid flow over a cylinder: a comparative study of steady and unsteady boundary layers (Journal of Naval Architecture and Marine Engineering, 2025)
This study aims to investigate the comparison of steady and unsteady MHD mixed convective nanofluid flow over a cylinder, taking into account various factors, including slip conditions, heat and mass transfer, heat generation, stretching ratio, thermal radiation, curvature, viscous dissipation, and chemical reactions. The analogous transformation technique is employed to transform nonlinear PDEs into a system of coupled ODEs, which are then solved using the Runge-Kutta fourth-order approach. The influences of numerous relevant parameters on the velocity, thermal, and concentration boundary layers (BLs) are illustrated graphically. Furthermore, the shear stress coefficient, Nusselt number, and Sherwood number are calculated for steady and unsteady flow conditions. The findings reveal that unsteady flow substantially influences the skin friction coefficient and the rate of mass transfer. Notably, the slip effect enhances these processes compared to steady flow; conversely, a contrary movement is observed in the heat transfer rate. It is observed that in unsteady flow conditions, the skin friction coefficient increases by 0.34%, and 0.04%, respectively due to the increase of power-law index and curvature; the Nusselt number decreases by approximately 0.2%, and 0.02% for increasing values of thermophoresis, and Brownian motion; as well as the Sherwood number decreases about 0.08%, and 0.05%, respectively for rising values of Schmidt number, and chemical reaction compared to steady flow. This research presents significant new insights into the thermal behavior of viscoelastic fluids, which have the potential to enhance heat transfer methodologies in industrial coating systems, chemical reactors, and polymer extrusion processes.Journal of Naval Architecture and Marine Engineering, 22(2), 2025, PP. 141-163